Perancangan dan Implementasi Sistem Peringatan Dini Banjir Berbasis IoT dengan ESP32, MQTT, dan Aplikasi Kodular - Ikhsan Afif Asrory; Muhammad Shifa; Moch Ali Imron Sya’roni; Budi Pramono Jati (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
Floods are the most frequent natural disasters and cause material and non-material losses. One of the problems faced is the lack of early warning when floods occur. This problem can be overcome with a flood early warning system. This paper discusses the solution to this problem, namely by designing and implementing a real-time flood early warning system using IoT-based Internet of Things (IoT) technology ESP32 MQTT and APK Kodular. The objective of this research, compared to previous studies, shows a gap in the methods used. While previous studies used an IoT-based flood warning system that sends data via SMS or an HTTP server, this study applies real-time monitoring with the MQTT protocol, which allows sending water level data with low latency to the Kodular application for faster and more responsive warnings. The method used is to connect hardware with IoT where ESP32 is a client that sends data to MQTT and will display it in the Kodular APK. This flood early warning system consists of: ultrasonic sensors, ESP32, MQTT cloud, OLED, buzzer, LED, and APK on the phone to receive notifications through a mobile application created using Kodular. This IoT-based system is installed in the Kudu Regency river and can monitor water levels in real-time. Based on a predetermined threshold, the system can activate the LED indicator or buzzer and send an early warning message to the user via the APK on the phone. Test results show that this system functions effectively in providing flood warnings with an accuracy of 1-2 cm and in a timely manner, making it suitable for community-based flood monitoring solutions